2008
DOI: 10.1177/0003319708318788
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity: Looking Into the Future

Abstract: A major concern related to childhood obesity is that obese children tend to become obese adults, with all the risks/ comorbidities associated (ie, diabetes, cardiovascular diseases among many others). The challenges of childhood obesity are not limited to one country but confront most nations around the world. Efforts to manage and to prevent childhood obesity involve education, research, and intervention. Research could drive new directions in prevention and could develop public policy that might help manage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…1 An increasing proportion of the world’s population is becoming obese, which is related to higher risks of morbidity and mortality. Childhood obesity has risen to significant levels globally and continues to increase in prevalence and severity.…”
Section: Introductionmentioning
confidence: 99%
“…1 An increasing proportion of the world’s population is becoming obese, which is related to higher risks of morbidity and mortality. Childhood obesity has risen to significant levels globally and continues to increase in prevalence and severity.…”
Section: Introductionmentioning
confidence: 99%
“…With more accurate methods such as MRI, it has been shown that an increased degree of VAT in males compared with females leads to decreased insulin sensitivity (20). Interestingly, there are already gender differences in body composition in children of school age (3, 21, 22), but whether this is also the case in preschool children has not been studied. This study aimed to investigate whether gender differences in abdominal fat distribution are apparent already in preschool children and to compare anthropometric measures of WC with data from DXA and MRI in this young population.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is described as a disease with genetic and environmental influence that may lead to several comorbidities such as type 2 diabetes, cardiovascular diseases (CVD), metabolic syndrome (MS) and respiratory abnormalities among others [1,2]. Since the discovery of its association with variants in intron 1 of the fat mass and obesity associated ( FTO) gene [3-5], many studies have been conducted to replicate this finding, to identify new variants, to clarify the biological function of the protein encoded and to explain its role in the origin and/or development of obesity [6].…”
Section: Introductionmentioning
confidence: 99%